Hubungan Kebiasaan Belajar dan Perhatian Orang Tua Terhadap Hasil Belajar Matematika Peserta Didik - Hermawan, Jody Setya; Yolanda, Dhea Rosa; Rapani, Rapani; Astuti, Nelly; Rohman, Fatkhur; Profithasari, Nindy (Universitas Negeri Makassar, 2024)
The purpose of this study was to determine a significant relationship between study habits and parents' attention to mathematics learning outcomes. This type of research is ex-post facto correlation. The population is 60 students, and is used as a research sample. Questionnaire data collection instrument with a Likert scale. Data analysis uses product moment correlation. It was concluded that the results of the study showed that there was a positive and significant relationship between study habits and parents' attention to mathematics learning outcomes indicated by a correlation coefficient of 0.575 which was at the